Biaxial failure response of composite laminates - Koh, Kelvin Chang Rong. (2013)
Fiber reinforced polymer composites are increasingly used in a variety of industries including aerospace, defence, sports and wind energy due to their high specific strength, stiffness and toughening mechanisms. The ability to mix and match material properties for composite laminates positions it more favourably over traditional engineering alloys like steel and aluminium. The uniaxial failure of composites under tension and compression is well understood along with competing failure modes. Large composite structures are generally made by wet-lay up techniques, which is prone to the presence of cracks. Despite the numerous strong attributes of composites, the anisotropic nature of the material makes it difficult to predict its failure response mode using existing models established for isotropic alloys. This report seeks to understand glass fiber reinforced plastics (GFRP) failure response under biaxial loading, crack sensitivity and its impact on strength of the material.